2019
DOI: 10.1371/journal.pone.0222629
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and associated factors among patients with breast cancer under chemotherapy at Tikur Anbessa specialized hospital, Addis Ababa, Ethiopia

Abstract: BackgroundBreast cancer is the most common cancer affecting women in Ethiopia with increasing burden, and chemotherapy treatment produces a detrimental effect on individual wellbeing. Since last few years quality of life has been the primary goal of cancer treatment, yet little research has been conducted on quality of life of breast cancer patients under chemotherapy.ObjectiveTo determine the quality of life and associated factors among patients with breast cancer under chemotherapy at Tikur Anbessa specializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
75
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 23 publications
17
75
1
4
Order By: Relevance
“…31,32 However, it is inconsistent with studies conducted in different countries. 19,25,26,28,[34][35][36][37] The level of quality of care might vary among care providers and even among institutions where the care was provided. For instance, a study conducted in northern Ethiopia proved that there was no radiotherapy in its area during the study.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 However, it is inconsistent with studies conducted in different countries. 19,25,26,28,[34][35][36][37] The level of quality of care might vary among care providers and even among institutions where the care was provided. For instance, a study conducted in northern Ethiopia proved that there was no radiotherapy in its area during the study.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the QoL is higher than the EORTC QLQ-C30 reference value 61. [19,20,22,24,31]. The study participants were different in Malaysian; chronic illness patients were included, in Morocco; received treatment for more than 3 months and severe neuropsychiatric disorders patients were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies show that; higher household income [23], older than 55 years of age, post-menopausal, stage I malignancy, patients who have completed treatment, and patients who underwent breast-conserving surgery were more likely to have a better QoL [24]. In a study in Black Lion hospital, educational status of college and above had good QoL than patients with no formal education, and divorced mothers were more likely to have good QoL than singles marital status [19].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations